Penggunaan Teknik Role Playing and Modeling untuk Meningkatkan Keterampilan Komunikasi Interpersonal Peserta Didik - Risky Desi Permatasari; Asrowi Asrowi; Edy Legowo (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This research aims to obtain data related to the Use of Role-Playing and Modeling Techniques to Improve Students' Interpersonal Communication Skills. The research method used is library research. The data analysis technique used is the content analysis reviewed from several references and literature. The results showed increased students' interpersonal communication skills after the intervention. This is evidenced by (1) The theoretical basis; (2) Purpose of use; (3) the successful use of role-playing and modeling techniques; (4) Implementation procedure; (5) The technique used; (6) learning objectives; (7) Recommendations for the use of role-playing techniques; (8) The relationship between the use of role-playing and modeling techniques in improving interpersonal communication skills by imitating and playing role play until these skills increase so that over time it will shape individual traits and behavior.